UPAYA GURU GENERASI Z DALAM MENYIKAPI KARAKTER SISWA GENERASI ALPHA DI MADRASAH IBTIDAIYAH WALISANGA II BANYUANYAR TENGAH (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has created generational differences in the field of education, particularly between Generation Z teachers and Generation Alpha students. These differences present challenges in the learning process, especially in maintaining student engagement and learning effectiveness. This study aims to describe the efforts of Generation Z teachers in addressing the characteristics of Generation Alpha students and to identify the challenges faced in the learning process at Madrasah Ibtidaiyah Walisanga II. This study employed a qualitative approach with a descriptive design. Data were collected through observation, semi-structured interviews, and documentation. The subjects of the study were Generation Z teachers, while the object focused on teachers’ efforts in responding to the characteristics of Generation Alpha students. Data were analyzed through data condensation, data display, and conclusion drawing, with triangulation techniques used to ensure data validity. The findings indicate that Generation Z teachers have implemented various adaptive strategies, including the use of varied and interactive learning methods, the utilization of technology-based media, flexible and communicative classroom management, and character building through habituation and role modeling. These efforts have been shown to enhance student engagement and interest in learning. However, teachers still face several challenges, such as maintaining student focus, managing heterogeneous classrooms, and the limited integration of technology in a pedagogical manner. This study highlights the importance of continuous teacher competency development in responding to the dynamics of student characteristics in the digital era, while maintaining a balance between instructional innovation and character education.